2007
DOI: 10.21273/horttech.17.2.195
|View full text |Cite
|
Sign up to set email alerts
|

Cold Storage to Control Codling Moth Larvae in Fresh Apples

Abstract: Codling moth [Cydia pomonella (Lepidoptera: Tortricidae)], found in exported apples (Malus sylvestris), can disrupt international markets. Cold storage at 1.1 °C was examined for possible control of three physiological larval states in ‘Fuji’ apples: diapausing (overwintering), diapause-destined, and nondiapausing. All nondiapausing larvae were dead within 12 weeks, diapaused-destined larvae were controlled by the seventh week, yet more than half of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Therefore, the implementation of a food safety concept is necessary [8][9][10][11] since these concerns can significantly affect consumers' choices [12]. In Taiwan, past scandals, including avian influenza cases (2015) [13], mad cow disease, dioxin defilement, high percentages of pesticides remaining on agriculture products (the 1990s) [14,15], a codling moth larvae outbreak (1990s) [16,17], and the prominence of footand-mouth disease (1997) [18,19], lessen citizens' trust in food safety [20]. Therefore, food-safety-oriented consumers must be guaranteed safety and quality as they become more selective in buying.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the implementation of a food safety concept is necessary [8][9][10][11] since these concerns can significantly affect consumers' choices [12]. In Taiwan, past scandals, including avian influenza cases (2015) [13], mad cow disease, dioxin defilement, high percentages of pesticides remaining on agriculture products (the 1990s) [14,15], a codling moth larvae outbreak (1990s) [16,17], and the prominence of footand-mouth disease (1997) [18,19], lessen citizens' trust in food safety [20]. Therefore, food-safety-oriented consumers must be guaranteed safety and quality as they become more selective in buying.…”
Section: Introductionmentioning
confidence: 99%
“…The remaining six larvae came from cold storage durations of 8 wk or less. Hansen et al (2007) found that cold storage of infested apples at 1.1ЊC all codling moth larvae destined to diapause were killed within 7 wk, and nondiapausing larvae were controlled within 12 wk. This is most likely the reason why no codling moth larvae have been detected by regulatory ofÞcials upon inspection in Taiwan after 19 December in any year (M. Willett, personal communication).…”
Section: Effect Of Harvest Date On Total Number Of Larvaementioning
confidence: 98%